(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article studies the words widely used in Central Asia in the XV-XX centuries and their lexical meanings. Semantic changes, peculiarities of the use of Chagatai words, the meaning of Chagataisms in the Kyrgyz dictionary and their current state are considered. The study uses historical comparative, descriptive and etymological methods of analysis, the evolution of words from Chagatai language in Kyrgyz language is comprehensively considered.